EDUCATIONAL PROCESSES CIRCLE NORMATIVE SOURCE VALUE OF DOCUMENTS - Nilufar Niyozova (Web of Journals Publishing, 2023)
In this article, the development of educational processes in the Republic of Uzbekistan, the essence of the source significance of normative documents specific to the system is revealed.
Keywords: education, upbringing, youth, Constitution, decisions, regulatory document, source, reform.